Avoidance as a learning strategy - Alonso Vázquez, María Cristina (Estudios Ingleses de la Universidad Complutense, 2005)
This article discusses avoidance as a learning strategy, and at the same time highlights the importance of this topic in SLA. The research study reported here is based on nine Spanish speakers’ attempts to learn the English negation system. The first section deals with the systematisation of the concept of avoidance, which has only relatively recently received attention in SLA research, and continues with an analysis of the different approaches to the topic and an examination of the limited number of empirical studies carried out so far. In the second section, findings on this topic from the empirical study mentioned above are presented. The extensive usage of avoidance by all of our subjects, and its cyclical character is highlighted. The article concludes by considering the use of avoidance in relation to three separate age groups, children, adolescents and adults.